SHQIPTAR GENOCIDE AGAINST SERBS FROM KOSOVO, WARTIME 1941-1943. LOVE THE LAND OF GREATER ALBANIA, THE TESTIMONY OF ILIJA MASLOVARIĆ (Heritage, 2024)
In the enclosure of the paper, we bring the testimony about the Serbs’ suffering in Kosovo and Metohia, namely in certain villages in municipalities Vučitrn, Lipljan, Kosovo Polje and Priština. The document is stored in the archives of the Eparchy of Raška Prizren, which has been relocated from Prizren to the Gračanica Monastery since 1999.
Keywords: Suffering of Serbs, Kosovo and Metohia, World War Second